FORMING IMPORTANT COMPETENCES OF ENGLISH TEACHERS IN THE PROCESS OF THEIR PROFESSIONAL TRAINING - Paziura, Nataliya (Mountain School of Ukrainian Carpaty, 2018)
The article presents the results of the analysis of the peculiarities in English teacher training, ensuring highly professional activity of teachers. The purpose and tasks of the study are to characterize the features of the practical formation of important competences of future teachers of the English language in the process of their professional training on a distinguished theoretical basis. Methodology of the study included descriptive methods (research, analysis and description of documents, scientific and educational sources) and a comparative method (identification of general and individual pedagogical patterns). Especially urgent is the question of the updating the contents of education in higher educational institutions according to the principles of personality-oriented approach targeted at development of teachers’ personality, their common and professional competence. It is directed at revealing progressive ideas in teachers’ professional development. Special attention is paid to the strengthening practical component in curriculum in the process acquirement of theoretical and practical knowledge and skills. The author has shown the necessary competences of a teacher of English: special, methodical, managerial, communicative, creative. The author concluded that it is necessary to study the peculiarities of teaching English in order to increase the effectiveness of training future teachers for professional activities.